Group Dynamics: Basics and Pragmatics for Practitioners - Haynes, Norris M. (University Press of America, 2012)
Keywords: Social groups; Group facilitation; dept.csp; dept.eco; faculty_collection

Counseling through images: using photography to guide the counseling process and achieve treatment goals - Ginicola, Misty M; Smith, Cheri; Trzaska, Jessica (Journal of Creativity in Mental Health, 2012)
Creative approaches to counseling help counselors to meet the needs of diverse populations. The utility of photography in counseling has been demonstrated through several case studies; however, clear implications of how photography relates to the counseling process have not been well delineated. The existing literature on phototherapy is reviewed and connected to specific photo directives within the counseling process and common psychotherapeutic techniques. © 2012 Copyright Taylor & Francis Group, LLC.
Keywords: counseling; creative counseling; dept.csp; photography; phototherapy